2007
DOI: 10.1080/00365540600798809
|View full text |Cite
|
Sign up to set email alerts
|

Unusual onset of varicella zoster reactivation with meningoencephalitis, followed by rhabdomyolysis and renal failure in a young, immunocompetent patient

Abstract: We present an unusual onset of meningoencephalitis due to VZV reactivation, with increased intrathecal production of IgG VZV antibodies and negative PCR, in a young, immunocompetent adult. Herpes zoster erupted 5 d later. Rare complication of VZV-related rhabdomyolysis occurred, with subsequent ARF, in combination with acyclovir and ceftriaxone. The patient recovered fully and remained healthy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…To our knowledge, only one study has reported meningoencephalitis with VZV-related rhabdomyolysis [1]. Pirounaki et al [1] reported a case of a 27-year-old immunocompetent man with meningoencephalitis followed by VZV-related rhabdomyolysis.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…To our knowledge, only one study has reported meningoencephalitis with VZV-related rhabdomyolysis [1]. Pirounaki et al [1] reported a case of a 27-year-old immunocompetent man with meningoencephalitis followed by VZV-related rhabdomyolysis.…”
Section: Discussionmentioning
confidence: 96%
“…Pirounaki et al [1] reported a case of a 27-year-old immunocompetent man with meningoencephalitis followed by VZV-related rhabdomyolysis. Some similarities and differences exist between this previous case and the present case.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations